Identification and Indicators of ERP Implementation Success Factor – a Literature Review - Warih Puspitasari; Muhardi Saputra; R Wahjoe Witjaksono (International Journal of Innovation in Enterprise System, 2021)
Enterprise Resources Planning has become one of the business and management applications that are believed to be able to improve the performance of companies and or organizations to be more efficient and effective. However, based on much research, the success rate of ERP implementation is questionable. Although the success of ERP implementation is often published in research, the failure rate of ERP system implementation is relatively high. Therefore, this study is to find out the problems and challenges faced by organizations in implementing ERP, by reviewing the existing literature on research on factors that influence the success of ERP implementation. The approach taken is to review several related research articles published in the 2015-2020 period from several publishers, namely Emerald Online, Science Direct, IEEE, and SAGE. The sample size for the last 5 years is expected to show the up-datedness of the data taken from the research article. New ideas that will emerge from this discussion are the main factors causing the success of ERP implementation for organization, so that they can be used to reduce the failure rate of ERP implementation in the future by proposing an ERP implementation model.